Avaliação de um sistema micro CHP experimental para veículos recreativos - Pinto, Daniel Vieira (Universidade do Vale do Rio dos Sinos, 2024)
Recreational vehicles (RVs) are homes on wheels that can be pulled by a motor vehicle, in the case of trailers, or can be self-propelled, like a motorhome. For comfortable use of an RV, there is a need for an electrical supply to recharge its batteries and operate the appliances and equipment installed, as well as thermal energy, for heating water and possibly air conditioning. A conventional and widely used solution for supplying electrical energy is the installation of photovoltaic modules combined with a connection to an electrical grid, when possible, although in some cases combustion engine generators are used. Water heating is generally done by means of gas-fired instantaneous heaters or hybrid gas/electric storage heaters. In general, air conditioning in RVs is done by means of split-type air conditioning and gas or diesel heating. In order to develop an alternative to the currently available energy supply methods, combined with the search for more efficient and environmentally friendly means of energy use, this work proposes the creation of a cogeneration system (heat and electric power) for RVs. A systematic literature review (SLR) was carried out, covering scientific articles on combined heat and power (CHP) systems. The SLR was preceded by a search for documents on cogeneration and energy use in RVs, both in scientific databases and in intellectual property banks. A research gap was identified on micro CHP devices for RVs. In the development of this work, an experimental micro CHP device (mCHP-Ex) was created, with 980 W of maximum electrical power, consisting of a single-cylinder internal combustion engine, an automotive alternator and heat exchangers for thermal recovery. The prototype was enclosed and instrumented, enablingmeasurements of the thermal power available in the water flow (from exhaust gases, lubricating oil and cooling air heat recovery systems) in addition to the electrical power of the alternator. To quantify the availability of electrical and thermal power, as well as the efficiency and operation parameters of the system, tests were performed in 46 different operating conditions, combining variations between 2000 rpm and 3600 rpm in the engine rotation frequency and the levels of electrical load imposed on the alternator, from no load to 100% load. The electrical efficiency of the mCHP-Ex reached 10.18% ± 0.2% at 3008 rpm with 83% load. Maximum electrical output was 0.746 kW ±0.015 kW at 3637 rpm and 100% load. Maximum thermal energy recovery rate was 3.267 kW ±0.039 kW. Utilization factor reached 65.57% ±0.22%. Compared to commercial micro CHP systems seen at RSL, mCHP-Ex can be up to 48% lighter. Compared to traditional means of providing separate electrical and thermal power for RVs, mCHP-Ex provides 63% greater primary energy utilization when the demand is for electrical power and space heating. However, for conditions where the demand is for electrical power and water heating, or even electrical power alone, current solutions available are still more efficient.
Keywords: Veículos recreativos; Sistema Micro CHP; Cogeração; Revisão sistemática de Literatura; Recuperação térmica; Recreational vehicles; Micro CHP System; Cogeneration; Systematic literature review; Thermal recovery; ACCNPQ::Engenharias::Engenharia Mecânica